Perception of working conditions on the quality of working life: Employees linked to health companies in Barranquilla, Colombia (2017)
Working conditions and their interaction on Quality of Working Life (QWL) perception in health sector employees from Barranquilla-Colombia were studied and modeled in a sample of 333 people aged between 16 and 73 years old. Reliability analysis, exploratory factor and principal components analysis with VARIMAX rotation, and binary logistical regressions was performed. Results show acceptable internal reliability of the scale (α = 0.996) and satisfactory adequacy of factorial matrix data (KMO = 0.934). Sixty-three items grouped into ten elements presented the factorial structure: four belong to working conditions and six to QWL. The results showed that occupational safety and psychosocial aspects positively affects the Quality of Working Life, with an overall classification rate of 92.2%. QWL in the health sector is a function of environmental variables, which can have an impact on the quality of the service and, therefore, on social welfare. © 2017 International Business Information Management Association IBIMA. All Rights Reserved.